Pengaruh Pemberian Fraksi Daun Jambu Biji Merah (Psidium guajava L.) terhadap Tebal Epitel Epididimis Tikus Putih Jantan (Rattus norvegicus) - Ayu Nina Mirania (Politeknik Kesehatan Tanjung Karang, 2019)
Population growth is increasingly showing alarming problems because it is not balanced with increasing welfare. Therefore we need population control, one of which is the implementation of family planning programs. The implementation of family planning is the responsibility of husband and wife. Plants that can make male antifertility are guava leaves. The purpose of the present research was to analyze the effect of feeding fractions of red guava leaves (Psidium guajava L.) on the epithelium thickness of epididymis of male white rat (Rattus norvegicus). The research was an experimental one, with a postest only control group design. The research sample size was 24 furrow male white mice Sprague Dawley, 60-80 days old. They were divided into 4 treatment groups, each being fed the fractions of n-hexane, ethyl acetate, and water-ethanol of guava leaves at a dosage of 80 mg/mouse/day, compared to CMC 1% for the control group for 48 days. The research findings showed that there was shrinkage of the epithelium thickness of caput epididymis (p=0,037), (p=0,001) in the corpus, and (p=0,001) in the cauda compared to the control group. It could be a conclusion that the fraction of guava leaves shrinkage the epithelium thickness of caput, corpus and cauda epididymis of male white rat (Rattus novergicus).